Valorization Strategies for a By-Product of Organic Tomato Processing as Potential Ingredient in Functional Food Formulations - López Bermúdez, Yhonattan Nicolás; Aldana Heredia, Juan Felipe; Sánchez-Camargo, Andrea del Pilar; Hernández-Carrión, María (Frontiers in Food Science and Technology, 2022)
Production of tomato-based products generates 5% of waste, composed mainly of peel. This has a significant amount of carotenoids, such as lycopene, and an appropriate amount of total dietary fiber (TDF). Both carotenes and dietary fiber are known to have functional effects on the human body. Therefore, the aim of this research was mainly divided into two parts. First, organic tomato peel obtained by a local processing industry was characterized in terms of percentage of macronutrients such as dietary fiber, protein, and ash, as well as total carotenoid content. Second, two valorization alternatives of these compounds as potential functional additives in food processing were proposed. The first one included carotenoid extraction using ultrasound-assisted extraction (UAE), the encapsulation of the enriched carotenoid extract using spray-drying technology, and its subsequent analysis of powder properties. The second one evaluated the potential use of TDF tomato peel as a replacement for fat and flour in four formulations of cookies. Each formulation was assessed using physicochemical, texture, sensory, and theoretical proximal analyses. The results revealed that UAE optimization was performed using a solvent ratio of 80:20 ethyl acetate:ethanol and 2.5% w/v of solvent:biomass ratio. The recovery percentage of total carotenoid content was 89.08%. The TDF content was 49.46 (3.91) g/100 g on a dry basis. For encapsulation, the drying yield and encapsulation efficiencies were 67.3% (0.5) and 58.1% (0.8), respectively. Sensory analysis showed no significant difference between the means for the control cookie and the 30% fat replacement cookie. Moreover, these 30% fat replacement cookies had the highest purchase intention by the consumers. This study presented a solution for unused tomato peel industrial byproducts, promoting the design of new functional food products with a high content of carotenes and dietary fiber, thereby increasing nutritional and health benefits for consumers.